Effects of Core Strength Training Using Stable Versus Unstable Surfaces on Lower Body Quality in 8th Grade Male and Female Students in a Junior High School in Bandung - Dwidarti, Sitti Juhana; Prabowo, Tertianto; Sungkar, Ellyana (International Journal of Integrated Health Sciences, 2018)
Objective: To investigate the effects of core strength training performed on stable (CSTS) compared to unstable surfaces (CSTU) on physical fitness in school-aged boys and girls.Methods: In this study, 72 (36 males, 36 females) untrained healthy subjects (mean age: 14±1 years, age range: 13–15 years) were randomly assigned to a CSTS group for stable surface (n = 36; 18 males and 18 females) or a CSTU group for unstable surface (n = 36; 18 males and 18 females). Core strength training performed on stable as compared to unstable surfaces were assessed on pre- and post-tests. Training period lasted 6 weeks (2 sessions/week). The components of physical fitness were assessed using standing long jump test,  stand-and-reach  test,  20-m  sprint  test, jumping  sideway test, and y balance  test.   Results: This study showed significant results in increased components of physical fitness in both CSTS and CSTU groups (p<0.05). The increase of physical fitness for CSTU was better than CSTS (p<0.05). There were differences of physical fitness between gender in both groups (p<0.05) except for stand-and-reach test (p>0.05).Conclusion: Core strength training performed on unstable and stable surfaces increases all components of physical fitness in youths. Core strength training performed on unstable surface can better improve the physical fitness compared to the stable surface. There were differences of physical fitness between gender in both groups except for stand-and-reach test.Keywords: Resistance training, physical fitness, gender DOI: 10.15850/ijihs.v6n1.1050